1993
DOI: 10.1152/ajpheart.1993.265.4.h1353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PDE inhibitors and carbachol on the L-type Ca current in guinea pig ventricular myocytes

Abstract: The phosphodiesterase inhibitors 3-isobutyl-1-methylxanthine (IBMX; 100 microM) and papaverine (100 microM) increased peak L-type Ca current (ICa) more than fivefold in a way similar to isoproterenol, forskolin, or intracellular adenosine 3',5'-cyclic monophosphate in guinea pig ventricular myocytes studied with the whole cell voltage-clamp technique at 22-24 degrees C. IBMX and papaverine could also induce a chloride current. Both drugs caused an apparent increase of ICa inactivation as revealed by 1) a negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Some of these PDE inhibitors have been shown earlier to increase I Ca by elevating [cAMP] i . For instance, application of IBMX leads to a large stimulation of basal I Ca in guinea-pig (Mubagwa et al, 1997), rabbit (Akita et al, 1994;Kajimoto et al, 1997) and human cardiomyocytes (Kajimoto et al, 1997). Similarly, we found that IBMX also increased basal I Ca in rat ventricular myocytes.…”
Section: Discussionsupporting
confidence: 78%
“…Some of these PDE inhibitors have been shown earlier to increase I Ca by elevating [cAMP] i . For instance, application of IBMX leads to a large stimulation of basal I Ca in guinea-pig (Mubagwa et al, 1997), rabbit (Akita et al, 1994;Kajimoto et al, 1997) and human cardiomyocytes (Kajimoto et al, 1997). Similarly, we found that IBMX also increased basal I Ca in rat ventricular myocytes.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast to superfusion of Mblue, internal dialysis with Mblue had no effects on the inhibition of Iso-stimulated I Ca by ACh at 1 and 10 M. However, inclusion of Mblue in patch pipettes has been reported to prevent the Iso-stimulated I Ca from muscarinic inhibition in rabbit nodal myocytes (14,15) and in rat ventricular myocytes (13). This antimuscarinic effect of Mblue was mimicked by inclusion of LY 83583 (14,15,39) or N G -monomethyl-L-arginine, a NOS inhibitor (13)(14)(15) in the patch pipette. On the basis of these results, it was concluded that the muscarinic inhibition of I Ca depended on the stimulation of the NOS/cGMP pathway.…”
Section: Discussionmentioning
confidence: 95%
“…Inhibition of PDE-III increases both cAMP and cGMP (Movsesian, 2002). If elevation of cAMP predominates, an increase in I Ca-L would be predicted (Mubagwa et al, 1993). However, if an increase in cGMP predominates in the vicinity of the L-type Ca 2ϩ channel in hamster myocytes, a decrease in I Ca-L may result.…”
Section: Discussionmentioning
confidence: 99%